Developing Business Intelligence System Based On Data Warehouse Using Pentaho For Procurement Process With Business Dimensional Life-cycle Methodology (case Study: Perum Bulog Divre Jabar) - M Firman Helmi Ariyansyah; Ari Yanuar Ridwan; Rachmadita Andreswari (eProceedings of Engineering, 2016)
In the agricultural sector, rice is the staple food of Indonesian society is important and can not be replaced. The price of rice became a barometer for other prices. If the price of rice goes up then the price of other goods would also be affected, thus leading to instability in various fields. Divre was important to meet rice supplies in each province. Then performance of divre should be monitored to see its development. Monitoring procurement performance with a look of fulfillment divre subdivre, realization contract partners and availability of goods that can be measured in value through realization of contract, is there divre are able to meet rice procurement in accordance with the target planning. Developing business intelligence using pentaho on the procurement process with business methods dimensional life-cycle is required to monitor procurement performance. By using the business intelligence, data contract realization divre particularly from aspect of performance availability and fulfillment of goods displayed into the dashboard. Dashboard of performance availability and fulfillment of goods are visualized informatively, so executive manager can read data more quickly and easily in monitoring and evaluating performance of appropriate rice procurement divre compliance of contract. Keywords: Business Dimensional Life-Cycle, Business Intelligence, Data Warehouse Procurement of Rice, Pentaho, Dashboard, Perum Bulog Divre Jabar